Profil Kadar Asam Urat Pada Penderita Diabetes Melitus Tipe 2 Terkontrol - Mutmainnah Abbas; Rosdiana Mus; Thaslifa Thaslifa; Olvyani Tira Layuk (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Type 2 Diabetes Mellitus (DM) is a metabolic disorder characterized by an increase in blood glucose due to decreased insulin secretion by pancreatic beta cells and or impaired insulin function (insulin resistance). Controlled Type 2 Diabetes Mellitus is a type 2 DM patient who takes preventive measures to avoid complications and death, such as adhering to medication, doing physical activity, controlling blood glucose levels to remain stable and implementing a healthy diet. Controlled type 2 diabetes mellitus aims to prevent complications, one of which is kidney function. One of the examinations to determine kidney function is uric acid which affects the increase in insulin levels. Uric acid is one of the metabolic that the amount should not be excessive in urine and blood. The purpose of this study was to determine uric acid levels in patients with controlled type 2 diabetes mellitus. The method in this study is a cross sectional study design with probability sampling technique. The results of the study of 30 research subjects with the lowest value of uric acid 2.29 mg/dL and the highest value of uric acid 6.92 mg/dL. The average uric acid value obtained in the research subjects was 4.58 mg/dL. These levels are still within normal levels, this can be influenced by controlling blood glucose levels, routinely doing physical activity, consuming food and drinks regularly and as recommended (healthy diet) and routinely consulting or taking medication so that the uric acid levels obtained are normal.